Initial neurite outgrowth in Drosophila neurons is driven by kinesin-powered microtubule sliding - Lu, Wen (2013)
Remarkably, forces within a neuron can extend its axon to a target that could be meters away. The two main cytoskeleton components in neurons are microtubules, which are mostly bundled along the axon shaft, and actin filaments, which are highly enriched in a structure at the axon distal tip, the growth cone. Neurite extension has been thought to be driven by a combination of two forces: pushing via microtubule assembly and/or pulling by an actin-driven mechanism in the growth cone [1, 2]. Here we show that a novel mechanism, sliding of microtubules against each other by the microtubule motor kinesin-1 provides the mechanical forces necessary for initial neurite extension in Drosophila neurons. Neither actin filaments in the growth cone nor tubulin polymerization is required for initial outgrowth. Microtubule sliding in neurons is developmentally regulated and is suppressed during neuronal maturation. As kinesin-1 is highly evolutionarily conserved from Drosophila to humans, it is likely that kinesin-1-powered microtubule sliding plays an important role in neurite extension in many types of neurons across species.